Modifikasi Mesin Pemupuk Elektrik Sebagai Pemupuk Padat Dan Cair Pada Tanaman - Safitri, Ita; Jamaluddin; Mukhlis, Andi Muhammad Akram (Jurnal Pendidikan Teknologi Pertanian, 2023)
This study aims to modify the electric fertilizer as a solid and liquid fertilizer that is uneven and uniform and difficult to operate in the fertilization process of plants. This research is descriptive research using the type of Research and Development (R & D) research. The tool testing mechanism is carried out in two stages, namely the solid fertilizer functional test and the liquid fertilizer functional test. Modifications of the electric fertilizing machine have been made on the basis of the design of the planned product drawings. Starting from the design of the drawings, then the manufacture of each component is assembled into a design to be made. The process of making tools consists of 3 stages, namely the manufacture of mechanical components, electrical components, and functional checks. The results showed that the fertilizing machine used could work well according to the wishes of the researcher, the theoretical field capacity produced in the testing process of fertilizing solid fertilizers with a land area of 4.8 m, namely 0.201 ha / hour. The average speed used is 1.4 m/s. The theoretical field capacity produced in fertilizing liquid fertilizer with an area of 4.8 m is 0.029 ha / hour with an average speed used of 1.4 m / s. The effective field capacity produced in the testing of the eletric fertilization machine as a solid fertilizer is 0.016 ha / hour and the effective field capacity produced in the testing of the liquid fertilization machine is 0.029 ha / hour. For effective field efficiency in testing electric fertilizing machines as solid fertilizers 7.96%, and effective field efficiency for liquid fertilizers is 14.42%